Biological and molecular characterization of bean bushy stunt virus, a novel bipartite begomovirus infecting common bean in northwestern Argentina - Reyna, Pablo Gastón (2021)
Common bean plants (Phaseolus vulgaris L.) showing different virus-like symptoms were collected in northwestern Argentina. Dot-blot hybridization tests showed that the begomoviruses bean golden mosaic virus and tomato yellow vein streak virus were the most prevalent, but they also revealed the presence of unknown begomoviruses. The complete genome sequence of one of these unknown begomoviruses was determined. Sequence analysis showed that the virus is a typical New World begomovirus, for which the name "bean bushy stunt virus" (BBSV) is proposed. Biological assays based on biolistic inoculations showed that BBSV induced leaf roll and stunting symptoms similar to those observed in the field-collected common bean sample.